Projeto de uma bancada didática para o estudo do escoamento em canal aberto para o Laboratório de Engenharia Mecânica - Campus Tucuruí - ARAUJO, Rafael de Sousa (2022)
The present work has the purpose of developing the structural design of a didactic bench of a multifunctional water channel for the Mechanical Engineering Laboratory (LABMEC), Tucuruí campus, with the objective of using it in disciplines and in research in the area of mechanics of fluids, in addition, to evaluate its resistance, through the analytical and numerical method. Analytical calculations were performed to determine volume, the forces exerted by the water and the load generated by the glass, the bending and shear stresses, in addition to the safety factor. For the numerical method, a structural analysis of the metallic structure with and without glass is performed using a finite element software. After performing the calculations and numerical simulation, these methods used corroborated for the bench to be considered safe.